Non-viral delivery of therapeutic microRNAs to glioma cells using chitosan nanocomplexes. (12th October 2019) - Boissinot, Marjorie; Limam, Sarra; Collado-González, Maria; Gonzalez-Espinosa, Yadira; Wurdak, Heiko; Goycoolea, Francisco M; Short, Susan C
Abstract: : One of the biggest challenges when treating brain tumours is achieving efficient delivery of therapeutic agents to the brain and more specifically to the cancer cells. MicroRNA-1300 was identified in our group as a very promising therapeutic microRNA given its cytotoxic effect when introduced in both established as well as cancer-stem-like patient-derived glioblastoma cultures, while not affecting differentiated glioblastoma cells. We are now collaborating to assess the potential efficiency of the natural biopolymer chitosan to form nanocomplexes containing the mature form of microRNA-1300 for delivery. Chitosan has been established as a highly attractive biocompatible polymer to deliver both in vitro and in vivo therapeutic nucleotides intracellularly. In previous studies, we have shown chitosan's efficacy to form spherical nanocomplexes with microRNA and apply them to the downregulation of JAMA-A mRNA in MCF-7 breast cancer cells. Chitosan can also be chemically conjugated to introduce affinity towards a wide range of cellular targets (e.g. with aptamers). Methods: We have optimised of the composition and characterised the biophysical properties of chitosan-microRNA nanocomplexes of varying (+/-) charge ratios using both a control nontargeting microRNA coupled to a fluorochrome (CS-miRdy547, efficiency of cell entry) and mature microRNA-1300 (CS-mi1300, efficient release and biological effect). We have tested the nanocomplexes in 2D monolayers and 3D spheroid cultures on established U251 as well as two patient-derived cultures. Reverse transfection was used as positive control. Results: The control nanoparticles of CS-miRdy547 are taken up by the patient-derived cultures in 2D and 3D. Analysis is ongoing using the CS-miR-1300 nanoparticles.